Analysis of Social Environment in Forming the Character of Elementary School Students - Muhammad Yusnan; Farisatma; Abdul Rahim; Acoci (Institute Journal and Publication Muhammadiyah University of Buton, 2024)
The social environment plays a crucial role in the process of forming student character. A conducive social environment can have a positive impact on students' moral and ethical development. Qualitative research is a research method that focuses on in-depth understanding of complex phenomena in real contexts. This approach is often used to answer complex questions and explore experiences, perceptions and meanings contained in them. The subjects of this research were 2 teachers, namely Class IV and Class V teachers. Qualitative data analysis is the process of systematically searching and compiling data. obtained from observations, interviews, field notes and documentation studies, organizing data into synthesis, compiling patterns, choosing what is important and what will be studied and making conclusions so that they are easy to understand. The research results show that social interaction, the role of the family, and the impact of the community environment around the school at Nganganaumala 1 State Elementary School are key elements in shaping students' character and moral values. Interactions that occur inside and outside the school environment provide opportunities for students to broaden their horizons about values ​​such as cooperation, empathy, and social responsibility. The role of the family as a model and supporter in the formation of positive attitudes and ethical values ​​also provides a strong foundation for students' personal. development